Transparency, Accessibility, and Teacher Perception of School Operational Assistance Fund Management - Muhammad Yasser; Wa Ode Rayyani (Review of Multidisciplinary Academic and Practice Studies, 2024)
Purpose: This study examines the influence of transparency and accessibility of School Operational Assistance (BOS) fund financial information on teacher perceptions in a public elementary school in Makassar, Indonesia, and evaluates whether these two constructs operate independently or complementarily in shaping stakeholder trust.Methodology: A quantitative explanatory design was employed using saturated sampling of all teachers at one SPF public elementary school. Of twenty distributed questionnaires, seventeen valid responses were analyzed through multiple linear regression with the assistance of SPSS.Results: Transparency did not significantly influence teacher perception (t=-0.009, sig=0.993), whereas accessibility exerted a positive and significant effect (t=4.320, sig=0.001). Simultaneously, both variables significantly influenced teacher perception (F=9.396, sig=0.003), explaining 57.3 percent of its variance.Conclusions: Accessibility, rather than transparency alone, is the dominant driver of positive teacher perception, although the two constructs jointly generate stronger explanatory power, reinforcing stakeholder theory's emphasis on usable information access.Limitations: The single-site design, small sample, and cross-sectional data restrict generalizability and causal inference.Contributions: The study extends financial accounting theory by positioning accessibility as a distinct antecedent of stakeholder perception rather than a mere extension of transparency, and offers practical guidance for schools and education authorities seeking to design more usable financial disclosure mechanisms for teachers as internal stakeholders of public education funding.